2016
DOI: 10.1093/glycob/cww025
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation of histone deacetylases 1 in hepatocellular carcinoma promotes cancer progression

Abstract: Hepatocellular carcinoma (HCC) is a malignant tumor originating in the liver. Previous studies have indicated that O-GlcNAc transferase (OGT) and histone deacetylase-1 (HDAC1) play important roles in the pathogenesis of HCC. In the present study, we investigated the physical link between OGT and HDAC1. The O-GlcNAcylation of HDAC1 is overexpressed in HCC. We found that HDAC1 has two major sites of O-GlcNAcylation in its histone deacetylase domain. HDAC1 O-GlcNAcylation increases the activated phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…This indicates that the regulation of O-GlcNAcylation and its controlling enzymes in various cancer cell lines may be different. However, previous research from our laboratory and others reported that augmentation of O-GlcNAcylation and OGT levels were associated with the malignant phenotypes of most cancers including breast (11,15), colon (12,16,17), liver (18)(19)(20) and prostate (21,22). It is noted that the regulation of O-GlcNAcylation is dynamic and may not be only dependent on the expression levels of its cycling enzymes (OGT and OGA) but also on its enzymatic activities (23).…”
Section: Discussionmentioning
confidence: 95%
“…This indicates that the regulation of O-GlcNAcylation and its controlling enzymes in various cancer cell lines may be different. However, previous research from our laboratory and others reported that augmentation of O-GlcNAcylation and OGT levels were associated with the malignant phenotypes of most cancers including breast (11,15), colon (12,16,17), liver (18)(19)(20) and prostate (21,22). It is noted that the regulation of O-GlcNAcylation is dynamic and may not be only dependent on the expression levels of its cycling enzymes (OGT and OGA) but also on its enzymatic activities (23).…”
Section: Discussionmentioning
confidence: 95%
“…Increased O-GlcNAcylation is observed in various tumors (Caldwell et al, 2010;Ferrer et al, 2014;Ma and Vosseller, 2014;Slawson et al, 2010;Zhu et al, 2012Zhu et al, , 2016, but its contribution to tumorigenesis is not well understood. Identification of Significance Increased O-GlcNAcylation is observed in cancer cells, but its contribution to tumorigenesis is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of CYP2E1 expression in response to deregulated histone modification which resulted in decline in apoptotic potential has been observed in alcohol-associated HCCs [136, 137]. Recent studies suggest that HCC progression can be repressed by inhibition of O-GlcNAcylation [138]. Epigenetic silencing of JMJD5 (jumonji C domain-containing protein 5), another tumor-suppressor gene in HCC pathogenesis, downregulates CDKN1A transcription to promote HCC cell proliferation [139].…”
Section: Histone Modificationmentioning
confidence: 99%